The community assembly of (sub)tropical macroinvertebrates significantly changes with functional groups and habitat degradation - Lu Wang; Hao Yang; Ci Chen; Linglin Wan; Tingting Zhou; Bo-Ping Han (Global Ecology and Conservation)
There is a consensus that both deterministic and stochastic processes shape the composition of biological communities. However, it is difficult to quantitatively disentangle their relative importance, which is fundamental for conserving and managing biological diversity. We examined the relative importance of deterministic and stochastic processes in the community assembly of macroinvertebrates in undisturbed and degraded streams by applying neutral community models (NCM) and calculating the normalized stochasticity ratio (NST). We focused on two dominant functional feeding groups with different traits: collector gatherers (small body size and weak dispersal ability) and predators (large body size and strong dispersal ability). The NCM showed that predator communities were largely shaped by deterministic processes (NCM R2 < 0.5), and collector-gatherers were mainly structured by stochastic processes (NCM R2 > 0.5). Stochastic processes in community assembly increased during the wet season due to frequent and intensive hydrological disturbances. Among undisturbed streams, community dissimilarity was primarily driven by stochastic processes (NST > 50 %), whereas in degraded streams, deterministic processes played a greater role (NST < 50 %). In other words, strong environmental filtering under intensive anthropogenic disturbance increased the influence of deterministic assembly mechanisms. In other words, the deterministic role increased with strong environmental selection under intensive anthropogenic disturbance. Analyses based on the occurrence and abundance data identified similar mechanisms underlying community assembly; however, the abundance data showed a stronger signal. Our study suggests that the relative importance of deterministic and stochastic processes in community assembly can change significantly depending on the functional groups and environmental disturbances.